Eficiência do processo de obtenção do biodiesel de girassol usando o catalisador KNO3/Al2O3 - Silva, Júlio César Teixeira da (2012)
It is known that the head office world energetics is leaning in the fossil fuels. However, the world panorama is changing quickly, for linked reasons to three of the humanity's great concerns in that century beginning: environment, global economy and energy. The biodiesel production is based on the transesterificação of vegetable oils or animal fats, using catalysts homogeneous or heterogeneous. The process of heterogeneous transesterificação presents lower conversions in comparison with the homogeneous, however, it doesn't present corrosion problems and it reduces to the occurrence of parallel reactions as saponification. In this sense, this work has for purpose the synthesis of a heterogeneous catalyst, KNO3/Al2O3, that soon afterwards was used in the reaction of transesterificação of the oil of the Helianthus annuus L. (sunflower). The solid materials (it supports and catalyst) they were analyzed by diffraction of ray-X (XRD) and electronic microscope of sweeping (MEV). After the analysis of Al2O3, a structure monophase amorphous tetragonal was verified, with characteristic patterns of that material, what could not be visualized in the difratograma of the catalyst. The biodiesel obtained with 4% wt. of KNO3/Al2O3 it was what obtained a better cinematic viscosity 8,3 mm2/s, comparing with the norms of ANP, and it also presented the best conversion tax in ethyl ésteres, in accordance with the quantitative measure starting from TG, that was of 60%. While the biodiesel with 6% wt. and with 8% wt. of KNO3/Al2O3 it was it that no transesterificou, because it was observed in the analysis termogravimétrica of those two materials, a single thermal event, that it corresponds the decomposition or volatilization of the triglycerides